التحليل بالعناصر المنتهية لانحناء سهم الرافعة التليسكوبي ذي المقطع المستطيل الأجوف بمساعدة الحاسوب - سمير كفا; رائد النجار; فادي طحان (Tishreen University, 2017)
يُستخدم الجائز الكابولي التلسكوبي بشكل واسع في العديد من أنواع الروافع. وباعتبار أن هذه الجوائز مرنة ويمكن تمديدها وتقليصها ضمن ظروف تشغيل مختلفة ، يتغير الطول الكلي للجائز ديناميكياً ، مما يؤدي إلى خصائص اهتزاز متغيرة مع الزمن. ما سبق يجعل عملية نمذجة الجائز أمراً صعباً على الرغم من الاحتياجات المهمة لهذه النمذجة بهدف تحليل الاجهادات والتشوهات أثناء عمل الرافعة بمساعدة برامج الـ CAD. يناقش هذا البحث إمكانية إيجاد حل للمشاكل التصميمية التي تنشأ أثناء انهيار سهم الرافعة التلسكوبي وذلك من خلال تطبيق تقنيات التحليل باستخدام العناصر المنتهية FEAوصولاً إلى الأبعاد المثلى للجائز والتي ستشكل التصميم الأمثل لسهم الرافعة التلسكوبي. The telescopic cantilever beam is widely used in different types of cranes. These structures are flexible; it can expand or shrink according to the operating conditions. The dynamic changes of the total length of the structure lead to time-dependent vibrational characteristics. In practice, CAD modeling for this case is a challenging matter due to the nature of the problem of analyzing stress and deformation occurring during the operation of the crane. This research discusses the feasibility of finding a solution for the design problems initialized during the failure of the telescopic cantilever beam through the application of Finite Element Analyses (FEA) in order to find the ideal dimension of the structure which represents the best design for the telescopic cantilever beam.